2023
DOI: 10.1093/brain/awad085
|View full text |Cite
|
Sign up to set email alerts
|

Thalamostriatal disconnection underpins long-term seizure freedom in frontal lobe epilepsy surgery

Abstract: Around 50% of patients undergoing frontal lobe surgery for focal drug-resistant epilepsy become seizure free post-operatively; however, only about 30% of patients remain seizure free in the long-term. Early seizure recurrence is likely to be caused by partial resection of the epileptogenic lesion, whilst delayed seizure recurrence can occur even if the epileptogenic lesion has been completely excised. This suggests a coexistent epileptogenic network facilitating ictogenesis in close or distant dormant epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…More recently, Giampiccolo et al (2023) performed a retrospective analysis of the patterns of disconnection associated with long-term seizure outcome in a series of 47 patients who underwent surgery for frontal lobe epilepsy. The Authors found a significant correlation between seizure freedom and disconnection of the anterior thalamic radiation and the cortico-striatal tract, indicating the role of these pathways in the development of novel epileptic networks at the base of seizure recurrence.…”
Section: Neurosurgical Implicationsmentioning
confidence: 99%
“…More recently, Giampiccolo et al (2023) performed a retrospective analysis of the patterns of disconnection associated with long-term seizure outcome in a series of 47 patients who underwent surgery for frontal lobe epilepsy. The Authors found a significant correlation between seizure freedom and disconnection of the anterior thalamic radiation and the cortico-striatal tract, indicating the role of these pathways in the development of novel epileptic networks at the base of seizure recurrence.…”
Section: Neurosurgical Implicationsmentioning
confidence: 99%
“…Similar to temporal lobe epilepsy, such concepts may be applied to other regions. Giampiccolo et al used tractography in 47 patients undergoing frontal lobectomy to identify the "disconnectome" and predict late seizure recurrence [33]. They found that long-term seizure freedom as durable as five years was associated with the disconnection of anterior thalamic and corticostriatal fibers.…”
Section: Network In Resective and Ablative Epilepsy Surgerymentioning
confidence: 99%
“…Modulating these nodes may potentially modify epilepsy transmission [17]. Epileptic patients have a network of connections in the brain associated with seizures, and by selectively interrupting specific pathways (such as the thalamus or striatum to the frontal lobe), may enable patients to achieve long-term freedom from seizures [18]. One of the principles of epilepsy surgery or deep brain stimulation (DBS) for epilepsy is to desynchronize the epileptogenic neural network by influencing the activity of key nodes in the epilepsy network [19].…”
Section: Introductionmentioning
confidence: 99%